Mengoptimalkan Media Sosial Untuk Meningkatkan Kesadaran Isu Global di Kalangan Remaja - Maulana, Arjun; Widiyanarti, Tantry; Hasan, Daffa Anugrah; Gymnastiar, Asyfa Davy; Luthfi, Rizqi Muhammad Fadhila; Azimah, Fauzan (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The development of digital technology and social media has changed the way youth interact and access information. With more than 4.26 billion social media users worldwide, these platforms have great potential to raise awareness among youth on global issues such as climate change, human rights and social conflict. This study aims to explore how to optimize the use of social media as a tool to raise youth awareness of global issues. The methods used in this research include surveys and interviews with adolescent social media users as well as content analysis of various social media platforms. The results show that social media can be an effective tool in disseminating information and encouraging active participation of young people in social activities. However, challenges such as the spread of false information and bias are also recognized as challenges that need to be overcome. This study recommends strategies to use social media wisely, including collaboration with influencers, awareness campaigns and media literacy education. In this way, young people can act as agents of change, strengthen intercultural understanding and solidarity, and create a more inclusive and tolerant world.